Efeito hipotensor e anti-hipertensivo do nitrato orgânico benzoato de 4-nitrooxibutila em ratos - Rocha, Patrícia Keytth Lins (2021)
Organic nitrates are commonly used in the treatment of cardiovascular disease. In this work, we verified the pharmacological effect of the organic nitrate 4- nitrooxybutyl benzoate (BBN) on the cardiovascular system of rats. The in silico approach was used to predict the biological activities for BBN using the PASS program; while the pharmacokinetic and toxicological properties were analyzed by pkCSM software; and the bioactivation process by molecular docking using Molegro program, which verified the interactions between BBN and the enzymes xanthine oxidoreductase (XOR), aldehyde dehydrogenase (ALDH), cytochrome P450 (CYP450) and glutathione S-transferase (GST). Then, an ex vivo approach was used to verify the effect promoted by BBN in PE (1μM) pre-contracted superior mesenteric artery isolated from rats. In addition, the BBN mechanisms of action and the development of vascular tolerance pre-exposing the mesenteric arteries to a high concentration of BBN (100 μM) were identifying. Among the mechanisms of action, using the inhibitor ODQ (10mM), the participation of the soluble guanylyl cyclase (sGC) enzyme was evaluated; the K+ channels was investigated using the blocker TEA (3mM); also, the inhibition of Ca2+ influx through Cav was analyzed by inductions of contractions with a depolarizing solution KCl (60mM) and with a selective agonist for CaV1, S(-)-Bay K 8644 (200nM). Finally, the in vivo approach was performed to verify the toxicological risk of BBN, administering high doses of the compound (300 or 2000 mg/kg) in rats; and the physiological effect on the cardiovascular system of rats was analyzed by administering intravenous doses of BBN (1; 5; 10; 20 mg/kg) in non-anesthetized rats. As a result of the in silico step, BBN was predicted as a potential vasodilator due to the release of the nitric oxide (NO) molecule from its compound; it was further suggested that BBN had good theoretical oral bioavailability and low toxicity; and interactions between BBN and XOR, ALDH, CYP450 enzymes were identified. In the ex vivo step, the vasorelaxant effect induced by BBN was confirmed. This effect is concentration-dependent and endothelium-independent. Vasorelaxation was significantly attenuated by the soluble sGC inhibitor, suggesting the involvement of the NO-GCs-PKG pathway. It was found that K+ channels were not involved with the BBN-induced effect. However, the inhibition of Ca2+ influx through CaV would participate in the effect promoted by BBN; since BBN was able to inhibit both the contraction mediated by Tyrode's solution with 60 mM KCl and the contraction promoted by S(-)-Bay K 8644. In addition, BBN did not develop vascular tolerance. In the assessment of acute toxicity, no deaths of rats were verified. Acute administration of BBN in rats induced a reduction in mean arterial pressure (MAP) and heart rate (HR) in normotensive and spontaneously hypertensive rats. These results indicate that BBN induces hypotensive and antihypertensive activities in rats.